Residents' Perceptions of Motorcycle Racing Events: A Social Exchange Theory Analysis - Endarman Saputra; David Iqroni; Roli Mardian; Wawan Junresti Daya (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study examines how the residents of Tanjung Jabung Timur Regency perceives motorcycle racing events at the Zabak National Circuit in Jambi Province, Indonesia. Applying the Social Exchange Theory framework, the research used quantitative data from a survey questionnaire. This method approach explores public opinions on motorsport events, identifying factors that shape these perceptions. The study anticipates a mixed public response, acknowledging both the perceived economic and social benefits alongside concerns about noise, safety, and environmental consequences. Factors such as economic opportunities, community pride, noise pollution, traffic congestion, and environmental degradation are expected to significantly influence public perception. Positive perceptions are likely linked to higher event participation, while negative perceptions may lead to reduced involvement and community resistance. By analyzing the complex interplay of perceived benefits and costs associated with motorcycle racing events, this study provides valuable recommendations for event organizers and local authorities. These recommendations emphasize maximizing economic and social benefits while minimizing negative impacts through effective noise control, traffic management, safety protocols, and enhanced environmental sustainability